Seven Pervasive Statistical Flaws in Cognitive Training Interventions - Moreau, David; Kirk, Ian J.; Waldie, Karen E. (Frontiers in Human Neuroscience, 2016)
The prospect of enhancing cognition is undoubtedly among the most exciting research questions currently bridging psychology, neuroscience, and evidence-based medicine. Yet, convincing claims in this line of work stem from designs that are prone to several shortcomings, thus threatening the credibility of training-induced cognitive enhancement. Here, we present seven pervasive statistical flaws in intervention designs: (i) lack of power, (ii) sampling error, (iii) continuous variable splits, (iv) erroneous interpretations of correlated gain scores, (v) single transfer assessments, (vi) multiple comparisons, and (vii) publication bias. Each flaw is illustrated with a Monte Carlo simulation to present its underlying mechanisms, gauge its magnitude, and discuss potential remedies. Although not restricted to training studies, these flaws are typically exacerbated in such designs, due to ubiquitous practices in data collection or data analysis. The paper reviews these practices, so as to avoid common pitfalls when designing or analyzing an intervention. More generally, it is also intended as a reference for anyone interested in evaluating claims of cognitive enhancement.